In vivo and in vitro sex differences in the dendritic morphology of developing murine hippocampal and cortical neurons - Kimberly P. Keil (Nature Portfolio, 2017)
Abstract Altered dendritic morphology is common in neurodevelopmental disorders (NDDs), many of which show sex biases in prevalence, onset and/or severity. However, whether dendritic morphology varies as a function of sex in juvenile mice or primary neuronal cell cultures is largely unknown even though both are widely used models for studying NDDs. To address this gap, we quantified dendritic morphology in CA1 pyramidal hippocampal and adjacent somatosensory pyramidal cortical neurons from male and female postnatal day (P)28 C57BL/6J mice. As determined by Sholl analysis of Golgi-stained brain sections, dendritic arbors of male hippocampal neurons are more complex than females. Conversely, dendritic morphology of female cortical neurons is more complex than males. In primary neuron-glia co-cultures from P0 mouse hippocampi, male neurons have more complex dendritic arbors than female neurons. Sex differences are less pronounced in cortical cultures. In vitro sex differences in dendritic morphology are driven in part by estrogen-dependent mechanisms, as evidenced by decreased dendritic complexity in male hippocampal neurons cultured in phenol red-free media or in the presence of an estrogen receptor antagonist. Evidence that sex influences dendritic morphogenesis in two models of neurodevelopment in a region-specific manner has significant mechanistic implications regarding sex biases in NDDs.